Organisational factors influencing teachers' inner sense of affective commitment to their schools in high- and low-accountability environments. (1st January 2015) - Christophersen, Knut-Andreas; Elstad, Eyvind; Turmo, Are
Affective commitment to a school organisation is a psychological link between a teacher and his or her school. The purpose of the article is to compare the statistical associations between organisational variables in a steering environment with assessment-based school accountability and in a steering environment without any assessments. We explore the link between the level of accountability and teachers' affective commitment. The results indicate that accountability has an indirect effect on commitment via its effect on leadership. The results indicate that principal-teacher relationships play an important role in fostering commitment in both low- and high-accountability environments.